Controversial Narratives : Young People in Estonia and The Singing Revolution - Sootak, Maria (My University, 2019)
This Master’s thesis explores the different narratives and the collective memory of the Singing Revolution (1987-1991) in Estonia. The analysis of the narratives includes a snapshot of the media coverage of the Singing Revolution, a brief overview of the secondary school history textbooks in comparison with the narratives by 15 people aged 20-24. The aim of the thesis was to discover whether a coherent narrative exists that can be attributed to the whole group of the 15 interviewees, to describe this narrative and to parallel it with the narrative provided by the analysis of the media and school books. The empirical data for this thesis consisted of media articles, school text books and interviews. The interviews were conducted from August 2017 to November 2018 in a semi-structured format. The data was subsequently organised and analysed using a combination of adapted methodologies of phenomenology, phenomenography and a framework introduced by Bert Vanhulle. The study found that there exists a common general narrative among the 15 interviewees with characteristic derivations among each individual. The interviewees often emphasised aspects of the Singing Revolution according to their own cultural group belonging. The narratives by the interviewees were in substance consistent with the narratives by the media and school books, the main difference was the orientation in time and space. The interviewees’ narratives were brief and often emphasised aspects of the Singing Revolution that the media and school books considered marginal. The brevitivity of the interviewees’ knowledge of the Singing Revolution should be considered when composing new curricula for history teaching in Estonia if the Estonian society aims to maintain the importance of the collective memory of the Singing Revolution.
Keywords: Singing Revolution, Estonian restoration of independence, collective memory, narrative, history teaching, recent history.